2004
DOI: 10.1016/j.cell.2004.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A Field of Myocardial-Endocardial NFAT Signaling Underlies Heart Valve Morphogenesis

Abstract: cells. Once transformed, the mesenchymal cells prolifer-1 Departments of Pathology and Developmental ate and invade the cardiac jelly, a basement membrane-Biology like substance elaborated by the myocardial cells. A Howard Hughes Medical Institute second process, which is even less well understood, 2 Cardiovascular Division begins after EMT. The endocardial cushion area elon-Department of Medicine gates and undergoes continuous remodeling that even-Stanford University Medical School tually refines the primitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
334
2
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(360 citation statements)
references
References 56 publications
18
334
2
6
Order By: Relevance
“…This speculation is consistent with recent findings reported by Chang and colleagues (Chang et al, 2004). In their study of murine valvulogenesis, they showed that NFAT signaling in the myocardium at E9 suppresses VEGF expression, producing conditions that initiate EMT.…”
Section: Discussionsupporting
confidence: 92%
“…This speculation is consistent with recent findings reported by Chang and colleagues (Chang et al, 2004). In their study of murine valvulogenesis, they showed that NFAT signaling in the myocardium at E9 suppresses VEGF expression, producing conditions that initiate EMT.…”
Section: Discussionsupporting
confidence: 92%
“…In silent heart mutants, AV endocardium remains squamous and does not express Dm-grasp, indicating the importance of cardiac function for the initiation of endocardial differentiation [24]. In contrast, Calcineurin signaling is not required for initial differentiation of the AV canal endocardium, but it is important for the subsequent epithelial to mesenchymal transformation that creates ECs [24,40]. Notch signaling, on the other hand, seems to be responsible for the spatial restriction of AV canal differentiation [24].…”
Section: Any Morphogenetic Rearrangement Of Embryonic Tissues Is Likementioning
confidence: 99%
“…Perhaps Ugdh is important for the control of Wnt signaling during EC formation: constitutive activation of Wnt signaling via mutation of the tumor suppressor gene apc leads to excessive EC formation beyond the boundaries of the AV canal, and overexpression of apc inhibits EC formation [39]. Other studies employing pharmacological inhibitors have suggested that Calcineurin/NFAT signaling promotes EC formation, while Notch signaling inhibits EC formation [24,40]. Additionally, a number of lines of evidence demonstrate that cardiac function plays a key role in the induction of ECs.…”
Section: Defining Cardiac Cytoarchitecture: Subcellular Mechanics Of mentioning
confidence: 99%
“…An example of developmentally regulated EMT occurs during the initial stages of cardiac morphogenesis. At embryonic day 9.5 (E9.5), endocardial cells undergo EMT ("endocardial EMT"); delaminating from the endothelial sheet, invading the matrix tissue called cardiac jelly, and engaging in endocardial cushion cellularization required for valve and septum formation (Chang et al, 2004). Because a number of congenital heart diseases are caused by abnormal atrioventricular canal (AVC) development (Bruneau, 2008), understanding of the molecular basis of AVC morphogenesis has been long sought, but still not fully achieved.…”
mentioning
confidence: 99%